From rationality to identity: the impact of using community health services for the aged on the well-being of older adults in China - Yang, Liu; Wang, Lijian (Frontiers in Public Health, 2024)
Objectives To better understand the outcome benefits of community health services for the aged (CHSA) and provide bottom-up identity for development, this study examined the impact of using CHSA on well-being of older adults from both objective and subjective dimensions. Methods Data from 1,411 people aged 60+ in Shaanxi, China was used in this study. The OLS estimate was used to analyze the impact of using CHSA on well-being of older adults. Then, the instrumental variable estimate was further hired to examine associations among variables to address the potential endogeneity concerns. The heterogeneity among disabled and non-disabled group was also estimated. Results For objective well-being, the mental health (β = 0.44) and financial well-being (β = 0.59) of older people using CHSA were significantly higher than those not using any service. The impact on objective well-being were more significant in non-disabled group. For subjective well-being, life meaning (β = 0.54) and security (β = 0.72) were positively associated with CHSA utilization, while independence index (β = −0.33) was negatively related with CHSA utilization. The subjective well-being of disabled group using services increased more than non-disabled group. Conclusion Findings underscore the positive, albeit group-selective, role of CHSA in improving well-being of older people in China and imply the necessity of high-quality development of CHSA and the targeted differentiation strategy.